ANALISIS DAN PERANCANGAN SISTEM E-PROCUREMENT PADA PT. XYZ - Akhmad, Teuku Adriansyah; Apriano, Dimas; Abdurachman, Edi (Journal of Business Strategy and Execution, 2011)
Digital technology and the Internet are very useful especially in data processing and communication. We examined the utility of this technology to improve the effectiveness and efficiency of the procurement system that we proposed to be used in the activities of the company PT. XYZ. PT. XYZ is in the business of machining high precision metal goods, producing precision products (safety parts) in the automotive industry, in huge numbers. We studied how the procurement system runs at PT. XYZ and determined that it could be more effective and meet objectives more efficiently by achieving precise specifications, with the right quantity, at the right time and the right price (most competitive). We obtained material for the development of the system that led to the proposal to use the procurement system with the utilization of internet technology, which we refer to as the E - Procurement system (Electronic Procurement) that we designed using the stages of the "waterfall“. Our hope is that this proposal could be utilized in PT. XYZ to support and strengthen its competitiveness and enable it to make greater contributions to the Republic of Indonesia.